Does international work experience pay off? The relationship between international work experience, employability and career success: A 30‐country, multi‐industry study. (11th December 2021) - Andresen, Maike; Lazarova, Mila; Apospori, Eleni; Cotton, Richard; Bosak, Janine; Dickmann, Michael; Kaše, Robert; Smale, Adam
Abstract: Drawing on human capital theory, our study examines the relationship between international work experience and individuals' career success in terms of promotions and subjective financial success. We propose that these relationships are mediated by external employability and hypothesise a moderating role of national‐level economic freedom. Using data from 19, 421 respondents, residing in 30 countries and working in different occupational groups (managers, professionals, clerical and blue‐collar workers), our results suggest that international work experience is positively related to promotions and subjective financial success across our study's different national contexts. These positive relationships were mediated by individuals' perceived external employability. Some support for the moderation of the relationship between international work experience and employability through economic freedom was only found when we differentiate between different types of international work experience. The findings enhance our understanding of the association between international work experience and career success from a human capital perspective.